2018
DOI: 10.1513/annalsats.201710-787oc
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Intensive Care Unit Readmission with Machine Learning Using Electronic Health Record Data

Abstract: A machine learning approach to predicting intensive care unit readmission was significantly more accurate than previously published algorithms in both our internal validation and the Medical Information Mart for Intensive Care-III cohort. Implementation of this approach could target patients who may benefit from additional time in the intensive care unit or more frequent monitoring after transfer to the hospital ward.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
132
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(140 citation statements)
references
References 42 publications
4
132
1
3
Order By: Relevance
“…One barrier to this approach is the challenge of harmonising the data, especially when combining data from different sources. This is one reason that we did not include diagnosis codes or severity of illness scores in this study, although they have previously been shown to be predictive of adverse events following discharge [11,12]. During a patient's stay in ICU, many of their physiological parameters are controlled by clinical intervention, and their expected physiological state is dependent on their medical history (see, for example, guidelines on acceptable levels of Hb in different patient types [38]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One barrier to this approach is the challenge of harmonising the data, especially when combining data from different sources. This is one reason that we did not include diagnosis codes or severity of illness scores in this study, although they have previously been shown to be predictive of adverse events following discharge [11,12]. During a patient's stay in ICU, many of their physiological parameters are controlled by clinical intervention, and their expected physiological state is dependent on their medical history (see, for example, guidelines on acceptable levels of Hb in different patient types [38]).…”
Section: Discussionmentioning
confidence: 99%
“…These tools range from criteria to evaluate discharge readiness [22,42], to guidelines for discharge planning and education [6]. Additionally, a number of risk models have been developed to predict adverse outcomes following ICU discharge [11][12][13]15,43]. In particular Badawi and Breslow demonstrated that mortality and readmission should be modelled independently as separate outcomes [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decision to discharge a patient from the ICU is usually based on clinical judgment using experience, clinical intuition, physiological parameters and scores to assess severity of illness and specific criteria, such as the need for mechanical ventilation or vasoactive medication [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Given the complexity of the decision and taking into account the vast amount of data gathered routinely in the ICU, machine learning is particularly suited for this task. Indeed, recent years have witnessed several attempts to develop these models [10,[15][16][17][18][19][20][21][22][23][24][25][26][27]. However, none of these models seem to have been specifically developed with the intention to directly implement them within the context of existing electronic health records to deliver real time decision support at the bedside.…”
Section: Introductionmentioning
confidence: 99%